2000
DOI: 10.1542/peds.105.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seating Position and Restraint Use on Injuries to Children in Motor Vehicle Crashes

Abstract: Rear seat position during a motor vehicle crash provides a significant protective effect, restraint use furthers this effect, and usage rates of restraint devices are low. The rear seat protective effect is in addition to and independent of the protection offered from restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 9 publications
5
49
1
5
Order By: Relevance
“…[5][6][7][8]10 Those studies all found unrestrained children (particularly those in the front seat) to be at the greatest risk of injury. The results from our multivariate analyses extend those of prior studies by providing additional details on the effects of age-appropriate restraint (not available in other national sources of crash data) and by examining the relative benefits of appropriate restraint and seating position for relevant age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8]10 Those studies all found unrestrained children (particularly those in the front seat) to be at the greatest risk of injury. The results from our multivariate analyses extend those of prior studies by providing additional details on the effects of age-appropriate restraint (not available in other national sources of crash data) and by examining the relative benefits of appropriate restraint and seating position for relevant age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Although most studies reported that restraint use in rear seats offers the greatest protection to children of any age, Braver et al 8 showed that older children with optimal restraint in the front seat were at lower risk of injury than were unrestrained children in the rear. In addition, the previous studies either did not contain sufficient detail for determination of the ageappropriateness of restraint use [5][6][7][8]10 or did not examine the benefits of appropriate restraint and seating position across a wide range of child ages 9,12 or crash types. 11 Information on the relative benefits of rear seating and appropriate restraint would assist policymakers faced with choices regarding provisions for rear seating or age-appropriate restraint when considering enhancements to state child restraint laws.…”
mentioning
confidence: 99%
“…10, 75,76 The authors of 1 of these studies specifically noted that the beneficial effects of the rear seat were no longer seen for children 13 years and older. 10 Thus, the AAP continues to recommend that all children younger than 13 years ride in the rear seat.…”
Section: Best-practice Recommendation: All Children Younger Than 13 Ymentioning
confidence: 99%
“…4 Despite the large number of resources allocated to media campaigns, infants and young children continue to travel unrestrained, in unsafe seating positions, and in front passenger seats of airbagequipped vehicles. [5][6][7] We anticipate that this may become more of a problem as vehicles are resold to second owners. As the fleet of airbag-equipped motor vehicles age, increasing numbers of low-income families who may have lower levels of education, inability to read and speak English, larger families, and fewer resources will be using these vehicles.…”
mentioning
confidence: 99%